Implementation of the Wadiah Agreement on the IB Mashlahah Savings Product at Bank BJB Syariah KCP Indramayu - Ibah Mahbubah (Kawakib: Journal of Multidisciplinary Research, 2025)
The IB Maslahah savings account is one of the savings products offered by Bank BJB Syariah KCP Indramayu. This product aims to provide a Sharia-based savings solution, adhering to the implementation of Sharia principles in managing savings by Sharia financial institutions. It employs the Wadiah Yadh Dhamanah contract principle, ensuring the security of customer funds and is intended for individuals or legal entities (Limited Liability Companies, Foundations, and Cooperatives). Under this contract, customers entrust their funds to the bank for safe storage without any obligation for the bank to provide a return. The recipient of the deposit (the bank) bears full responsibility for the entrusted funds and is obligated to return them in full if the customer decides to withdraw the funds or items at any time. This research aims to explore the implementation of the IB Maslahah savings product at Bank BJB Syariah KCP Indramayu, describe the mechanism of the Wadiah contract in managing the IB Maslahah savings product, and uses a descriptive qualitative method. The data were obtained through interviews with one of the bank's employees and field observations of the Wadiah contract implementation in the IB Maslahah savings product.